ESENSI KEBERADAAN ADVOKAT MENURUT HUKUM ISLAM - Arifin Rada (AHKAM : Jurnal Ilmu Syariah, 2014)
Essence of Advocate Existence Based on Islamic Law. Advocate is a person who provides legal assistance, in the court as well as outside of the court based on the Law. The legal services given such as legal advice, legal aid, and any other acts, are aimed to represent client’s interest. Advocates have multi tasks to be accomplished, from simply giving people advice to struggling the rights of persons deprived of their rights. Islam pay attention to legal matter as well as the status and the mandate given to a person to another one (advocate). Islam recognize al-wakâlah due to people need it.DOI: 10.15408/ajis.v14i1.1248